Assessing the physiological responses of the gastropod Crepidula fornicata to predicted ocean acidification and warming. (6th November 2015) - Noisette, Fanny; Bordeyne, François; Davoult, Dominique; Martin, Sophie
Abstract: Organisms inhabiting coastal waters naturally experience diel and seasonal physico‐chemical variations. According to various assumptions, coastal species are either considered to be highly tolerant to environmental changes or, conversely, living at the thresholds of their physiological performance. Therefore, these species are either more resistant or more sensitive, respectively, to ocean acidification and warming. Here, we focused on Crepidula fornicata, an invasive gastropod that colonized bays and estuaries on northwestern European coasts during the 20 th century. Small (<3 cm in length) and large (>4.5 cm in length), sexually mature individuals of C. fornicata were raised for 6 months in three different p CO2 conditions (390 μatm, 750 μatm, and 1400 μatm) at four successive temperature levels (10°C, 13°C, 16°C, and 19°C). At each temperature level and in each p CO2 condition, we assessed the physiological rates of respiration, ammonia excretion, filtration and calcification on small and large individuals. Results show that, in general, temperature positively influenced respiration, excretion and filtration rates in both small and large individuals. Conversely, increasing p CO2 negatively affected calcification rates, leading to net dissolution in the most drastic p CO2 condition (1400 μatm) but did not affect the other physiological rates. Overall, our results indicate that C. fornicata can tolerate ocean acidification, particularly in the intermediate p CO2 scenario. Moreover, in this eurythermal species, moderate warming may play a buffering role in the future responses of organisms to ocean acidification.